2015
DOI: 10.1002/etc.3022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ester metabolites from petroleum hydrocarbon biodegradation in groundwater using GC×GC‐TOFMS

Abstract: Abstract:In an effort to understand the nature and toxicity of petroleum hydrocarbon degradation metabolites, 2-dimensional gas chromatography linked to a time-of-flight mass spectrometer (GCÂGC-TOFMS) was used to conduct nontargeted analysis of the extracts of 61 groundwater samples collected from 10 fuel release sites. An unexpected result was the tentative identification of 197 unique esters. Although esters are known to be part of specific hydrocarbon degradative pathways, they are not commonly considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Mohler et al () were able to match 750 compounds to known standards but this represented only 23% of the total ion chromatogram. Some of these compounds have been identified as alcohols, organic acids (Cozzarelli et al ), aldehydes, ketones, and esters (Zemo et al ; O'Reilly et al ), but Mao et al () identified complex structures with multiple oxygen molecules that are not readily placed into these categories. The majority of the compounds identified in these studies have carbon numbers less than 18 carbons whereas at Bemidji, the partial degradation products recovered have carbon numbers per average molecule of 18 and higher (Thorn and Aiken ), so metabolites in crude oil plumes may differ from those in gasoline plumes.…”
Section: Discussionmentioning
confidence: 99%
“…Mohler et al () were able to match 750 compounds to known standards but this represented only 23% of the total ion chromatogram. Some of these compounds have been identified as alcohols, organic acids (Cozzarelli et al ), aldehydes, ketones, and esters (Zemo et al ; O'Reilly et al ), but Mao et al () identified complex structures with multiple oxygen molecules that are not readily placed into these categories. The majority of the compounds identified in these studies have carbon numbers less than 18 carbons whereas at Bemidji, the partial degradation products recovered have carbon numbers per average molecule of 18 and higher (Thorn and Aiken ), so metabolites in crude oil plumes may differ from those in gasoline plumes.…”
Section: Discussionmentioning
confidence: 99%
“…Mohler et al () listed 768 TICs that occurred in source area and downgradient samples from five fuel terminals ( n = 22), but information was not presented as to how often the specific individual compounds had been detected or how the mixture of individual compounds differed between samples. O'Reilly et al () listed individual esters tentatively identified in 61 samples. Results are now available from 113 groundwater samples collected from 51 monitoring wells at 17 fuel terminals and 5 service station sites.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a nonaqueous‐phase liquid (NAPL) has been shown to act as an additional partitioning phase for PAHs and PCBs , with sediment–water distribution coefficients ( K d ) gradually increasing at oil concentrations above those resulting in a NAPL . The bioavailability of petroleum hydrocarbon constituents via the soil pore‐water will be a function of their partitioning behavior between water, the soil organic carbon, and the NAPL (see also http://www.api.org/~/media/Files/EHS/Clean_Water/Bulletins/14_Bull.pdf).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of partitioning to a NAPL is dependent on the amount of NAPL present . Thus, the bioavailability of petroleum hydrocarbons, and their toxicity on a soil concentration basis, will depend on the size of a NAPL present.…”
Section: Discussionmentioning
confidence: 99%